The English language needs of hospitality students in a polytechnic / Nik Intan Baizura binti Ramsa - Nik Intan Baizura, Binti Ramsa (2014)
The study was conducted to ascertain students’ English language needs for Hospitality courses from the Hotel & Catering and Tourism Management programmes in Polytechnic of Johor Bahru (PJB) which is officially known as Politeknik Ibrahim Sultan (PIS). The research was specifically designed to focus on students’ lacks and needs of English language skills during industrial training in order to prepare them for occupational purposes. This study also intended to determine students’ problem in terms of linguistic competence during internship. For the purpose of this study, 171 students, four lecturers and seven key personnel were involved. Questionnaires and interviews were used as the main instruments for this study. The results gathered may also be of interest to curriculum developers of Malaysian polytechnics, lecturers and trainers for pedagogical reasons to help them develop more effective teaching and learning strategies and materials. The implications of the findings for the individual student, institution and the technical and vocational education system as a whole constitute an important perspective of the research effort.